Learning Document Design For New Employees In Scooter Layur Workshop Using Seci And Addie Methods - Fadhal Nafi Pratama; Augustina Asih Rumanti; Nurdinintya Athari Supratman (eProceedings of Engineering, 2020)
Abstract Scooter Layur Workshop is a company engaged in the European scooter workshop. Many scooters come to Scooter Layur Workshop, but Vespa 3V and Vespa Iget are the scooters who do the most of this workshop. Scooter Layur Workshop Has five mechanics, two of which are senior mechanics. In the Scooter Layur Workshop has two new mechanics who do not understand how to service and maintain a European scooter. This causes delays in service and maintenance processes because new mechanics have to ask senior mechanics; it creates delays for senior mechanics and mechanics. In the need for all media to learn for new mechanics, a media that helps for knowledge sharing is a learning document. From the available data, seven service and maintenance processes are taken most often by mechanics, so there are seven types of service and maintenance that will be made into learning documents. This study uses the SECI (Socialization, Externalization, Combination, and Internalization) method to create learning document content, namely by exploring the knowledge and experience of two senior mechanics. There is a difference in knowledge between the two senior mechanics after that the FGD and brainstorming are done to determine the best process. The result is the basis for making learning documents. ADDIE method is used to create learning documents. From the evaluation results obtained by mechanical knowledge increased after the existence of a learning document in terms of the value of the quiz. Keyword : FGD, Brainstoming, ADDIE, SECI, Leaning Document